Becoming a mother: perspectives and experiences of young women in a South African Township. Issue 2 (1st February 2018) - Mjwara, Nompilo; Maharaj, Pranitha
Abstract: There has been growing interest in the high levels of pregnancy among young women in South Africa. This study aimed to explore a range of perspectives and experiences of early motherhood among young women in a township in KwaZulu-Natal, South Africa. This was done using in-depth interviews from a small sample of young mothers aged 18–24 years. All the young mothers reported that they had had their first child while still at school. None of them had intended or planned to have a child, and were therefore not ready for motherhood. Limited information on pregnancy prevention methods plays a key role in influencing early childbearing. Young mothers in the study wanted to assume financial responsibility for their children but they were finding it difficult to do so. Many faced numerous obstacles as they were no longer in a relationship with the father of their child and depended on their own parents for support. Participants described how the difficulties they faced in their daily lives and their new roles as mothers impacted negatively on their education and career aspirations. The study recommends greater involvement of schools and community in addressing the challenges of early childbearing.